Hemostatic Management of Extracorporeal Circuits Including Cardiopulmonary Bypass and Extracorporeal Membrane Oxygenation - Fang, Zhe Amy; Navaei, Amir Hassan; Hensch, Lisa; Hui, Shiu-Ki Rocky; Teruya, Jun (Seminars in Thrombosis and Hemostasis, 2020)
Cardiopulmonary bypass and extracorporeal membrane oxygenation (ECMO) cause hemostatic derangements that can predispose patients to both bleeding and thrombotic complications. Often, patients present for urgent surgery while taking medications including antiplatelet agents, vitamin K antagonists, and direct oral anticoagulants, which must be recognized, monitored, and managed. During extracorporeal circulation, appropriate anticoagulation, most commonly with heparin, is required to maintain blood flow and avoid thrombotic complications. However, anticoagulation and other effects of extracorporeal circuits can also have an undesired consequence of bleeding. Extracorporeal circulation leads to coagulopathy that may require therapy with blood products such as platelets, cryoprecipitate, and plasma in case a patient bleeds. Platelet dysfunction related to exposure to a foreign circuit is a primary concern, as is the development of acquired von Willebrand syndrome, which frequently remains undetected on routine testing. Hemorrhagic complications in ECMO, such as intracranial hemorrhage, pulmonary hemorrhage, and hemithorax, can occur. Hemostatic agents including antifibrinolytics, desmopressin, fibrinogen concentrates, and other factor concentrates may be needed to achieve hemostasis in these often-challenging patients. Managing bleeding on extracorporeal support requires careful monitoring and a thoughtful approach.
Keywords: cardiopulmonary bypass; CPB; extracorporeal membrane oxygenation; ECMO; bleeding; review